Effect of financial knowledge on the willingness to pay for micro-insurance among commercial market business operators in Kasoa, Ghana - Wordzro, Leonard (University of Cape Coast, 2025)
The objective of the research was to examine the influence of financial literacy on the propensity of commercial market entrepreneurs in Kasoa, Ghana, to invest in microinsurance. This investigation employed an explanatory research framework, underpinned by a quantitative methodological approach. Commercial market vendors that trade at the Kasoa Main Market were among the target population. Operators of commercial markets that sell in the Kasoa Main Market were sampled and polled for the study. In order to execute the investigation, primary data was acquired through the utilization of a structured questionnaire. The results of the investigation indicated that proprietors of commercial market businesses operating within the Kasoa Main Market generally exhibited a commendably elevated level of financial literacy. Furthermore, the findings revealed that among commercial market business operators in Kasoa, Ghana, there exists a statistically significant positive moderate linear correlation between financial awareness and the propensity to pay. Moreover, the study demonstrated that financial literacy possesses a statistically significant predictive capacity to engender a positive yet substantial variance in the willingness to pay for microinsurance. It was therefore recommended that commercial business operators implement targeted educational programs to enhance the financial knowledge of CMB operators, focusing on specific areas identified in the study and collaborating with insurance companies and industry associations to provide workshops, seminars, and informational materials.
xi,95p:,ill
Keywords: Commercial Market Business Operators Financial Knowledge Microinsurance Willingness to Pay